Tinospora Cordifolia, A Rasayana Herb, as a Potential Source of Infectious Disease Therapeutics - Paliwal, Paras; Islam, Muneeb ul; Sharma, Shweta; Sharma, Anuradha (Current Traditional Medicine, 2025)
IntroductionAyurveda is a well-established traditional medicinal system in India which focuses on the treatment of chronic illnesses and the promotion of overall wellness. A significant upsurge has been observed in the research and development of traditional medicine in the 21st century. Tinospora cordifolia is a valuable Rasayana herb of Ayurveda with various medicinal properties like anticancer, antiobesity, hepatoprotective, antiulcer, antimicrobial, and immunomodulatory.AimThe current study aims to review the antimicrobial potential of T. cordifolia based on a number of available scientific evidence.MethodologyLiterature was retrieved from PubMed, Google Scholar, and other databases with a combination of different keywords, including antimicrobial, antifungal, antiviral, antiparasitic, immunomodulatory, antioxidant, antiinflammatory with T. cordifoli, and the obtained reports were analyzed.ResultsVarious studies indicate the antimicrobial potential of this herb against different viral, bacterial, fungal, and parasitic pathogens. Majority of the available evidence includes the preliminary screening of the antimicrobial activities. To highlight the societal acceptance of T. cordifolia in this context, some value-added products based on this herb have also been discussed briefly.ConclusionT. cordifolia has antimicrobial potential, which could be explored for the development of natural products-based therapeutics for infectious disease treatment. Cytotoxic, antioxidative, anti-inflammatory and immunomodulatory properties of T. cordifolia contribute to minimizing microbial colonization and strengthening the immune system against emerging infections. Herbal medicines are associated with some limitations, such as low effectiveness, seasonal variations of phytochemicals etc. More detailed studies are required to understand the underlying mechanism and the responsible phytochemicals, which will enhance the translational value of T. cordifolia-based phytotherapeutics.
Keywords: immunity booster